Pauia Deb et Dutta- a Remarkable New Genus and Species from Tirap Frontier Division - Deb, D. B.; Dutta, R. (Indian Forester, 1965)
Pauia Deb et Dutta gen. nov. (Family Solanaceae-Tribe Atropeae) is described with illustrations. This plant was collected by the senior author on way to Wakka (about 6 KM away at about 2,100 malt.), Tirap Frontier Division, N.E.F.A., India, on 2-7-61. The new genus (monotypic) is named in honour of Rev. Dr. H. Santapau, Director, Botanical Survey of India, Calcutta, as a token of deep regard and gratitude. The general appearance of the plant particularly the habit and the leaf, indicates apparent similarity with Indian Belladonna namely Atropa acuminata Royle ex Lindley. Hence the specific name is selected after that plant.